PENERAPAN ANALISIS SWOT DALAM MENINGKATKAN PENJUALAN “SIOMAY PAK BLANGKON”JEMBER - Dinarso, Rahmat Cahyo; Haryono, Rudi; Dharma, Rendra Adi; Kusuma, Hendra; Qomariah, Nurul (Fakultas Ekonomi dan Bisnis, 2022)
The increasingly fierce level of business competition currently means that business actors need to have a strategy in order to survive and develop. Companies and micro businesses need to implement effective marketing strategies to increase sales. This marketing strategy can also prepare yourself to face increasingly fierce competition from other competing businesses. By using a SWOT analysis, a business can determine what needs to be improved both internally and externally to ensure work operations run smoothly. This research aims to see the application of SWOT analysis to the factors that influence sales and to analyze the application of SWOT analysis in increasing the sales volume of